Digital Document Security System Ministry of Defense uses the Advance Encryption Standard (AES) Method - Sutomo, Muhammad; Krisnanik, Erly (Fakultas Ilmu Komputer UPN Veteran Jakarta, 2018)
Information is a valuable asset that must be managed properly by individuals,government and private organizations. Therefore the security of information becomesvery important. The Indonesian Ministry of Defense requires security of validdocuments, especially classified letters that are distributed through electroniccommunication facilities, carried out by a unit called the Ministry of Defense'sPassword Room. The purpose of the document coding is 1) to provide convenience,speed and security in the distribution of letters given the wide distribution of thelocation of the Ministry of Defense Work Unit Office; 2) Efficiency of the stages ofprocessing letters from receipts to shipments to the satker's address can be shortenedand 3) Speeding up the data search process and providing convenience for leaders tocarry out monitoring and analysis of strategic information. Based on this, theresearcher built the Ministry of Defense Document Coding Information Systemmanaged by the Password Room using the Advance Encryption Standard (AES)method to increase security from possible information leakage / theft. The techniqueused in AES uses substitution (S-boxes) directly on the document using a largerencryption key that is 256 bits. The results of this study are an integrated Ministry ofDefense digital document security system.